UNLOCK-C: um jogo sério 3D para apoio ao ensino e aprendizado da linguagem de programação C - SANTOS, Marcos Antônio Pacheco dos (2016)
The growing influence of computing on human society makes it increasingly important the teaching of computer programming in computer sciences undergraduate courses or technological courses. Nevertheless, the low level of motivation of many students, the complexity of the subject and the traditional way of teaching are barriers for learning these disciplines. In order to mitigate these barriers ,in this context, a type of software called serious game was developed, as a tool to help teach programming languages. Serious games are digital games that have a specific purpose other than just entertainment. Serious games have received significant attention among researchers. In particular, there have been research toward developing serious games that enrich the teaching and learning process of programming disciplines of computers and programming languages. However, many developed educational games have serious dull narrative and gameplay that are lacking compared to the sophisticated 3D games usually played by students. Regarding the construction of these educational serious games, although there are software development methodologies applicable to this type of game, there is no consensus on which methodology to use. This dissertation proposed the use of an educational serious game with three-dimensional (3D) sophisticated, more in line with gender digital 3D games, played by digital native students. The game was developed by a custom software development methodology optimized from other educational serious games development methodologies. The game was used in undergraduate classrooms, as a teaching and learning tool related to computer programming disciplines, focusing on the C language. Preliminary results showed an increase in motivation and interest of students in relation to the learning of the content. Thus, this serious game can be used as a teaching and learning tool as a way to get more data on the problem and simultaneously trying to improve the level of motivation and interest of students about the C language and computer programming concepts.